Enhancing economic flexibility: what is in it for workers? - Cournède, Boris; Denk, Oliver; Garda, Paula; Hoeller, Peter (Paris, 2016)
"Reforms that boost growth by enhancing economic flexibility often meet strong opposition related to concerns that they may imply adverse consequences for categories of workers. This study investigates how making product or labour market regulation more flexible changes workers’ risks of moving out of employment and jobless people’s chances of becoming employed. To do so, it employs specially harmonised micro-level data covering individual workers in 26 OECD countries. The micro-econometric regressions reveal that labour market reforms do not uniformly influence transitions in and out of employment but that their effects vary depending on institutions and other policy settings. For instance, making employment protection of regular contracts more flexible is associated with more transitions into employment in countries that have above-average activation programmes. As for product market reforms, they are found to boost transitions into employment, especially for women, and to have no systematic effect on exits, so that overall they tend to boost aggregate employment, in line with earlier evidence. The micro-data show that workers with low earnings potential, who, already before reforms, experience much higher transition rates in and out of employment than other groups, face particularly strong increases in employment churn when product market regulations become more flexible. Additional micro-econometric analysis focusing on sectors subject to specific product market regulation (energy, transport, communication) reveals that workers employed in tightly regulated sectors typically earn more than their peers with similar characteristics working elsewhere. Taken together, the findings can help enhance reform design, in particular by highlighting the benefits of (a) policy packages drawing on complementarities between product and labour market reforms, (b) active labour market programmes that effectively support more vulnerable workers and (c) broad reforms over narrow compensation schemes."